4p+2p+6p-1=

Simple and best practice solution for 4p+2p+6p-1= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4p+2p+6p-1= equation:


Simplifying
4p + 2p + 6p + -1 = 0

Reorder the terms:
-1 + 4p + 2p + 6p = 0

Combine like terms: 4p + 2p = 6p
-1 + 6p + 6p = 0

Combine like terms: 6p + 6p = 12p
-1 + 12p = 0

Solving
-1 + 12p = 0

Solving for variable 'p'.

Move all terms containing p to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 12p = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 12p = 0 + 1
12p = 0 + 1

Combine like terms: 0 + 1 = 1
12p = 1

Divide each side by '12'.
p = 0.08333333333

Simplifying
p = 0.08333333333

See similar equations:

| 7x-20=29 | | Ma-Th=fun | | -10x+10=-10 | | (4x^2)(-2x^3y^5)(-3xy)=0 | | 5x*5x= | | r(x)=-0.11x^2+100x | | 5n-18=-33 | | -5x+-30=80 | | 3(5z-3)-3(-2z)=6 | | 2(x-1)=3x-(x+2) | | 6s-15=-6+5a | | 9t-22=-29+8t | | -11x-31=-20 | | .5y+7=.75y-4 | | 32=(x-7)(x+7) | | 5(6c-4)+3(8c-1)= | | 2(3+5x)-5=31 | | 74-4x=14x+24 | | 15-2(w+5)=11 | | X+24=130 | | 11x-31=-20 | | x+9.8=14.5 | | 7=y-12 | | 3x-17=16-(2x+8) | | 2x+12=90+3x+23 | | 30x+3=123 | | 16x+420=-100 | | 7-2=13-3 | | 4(y+3)+7=4y+19 | | 22=5x+7 | | X^3-2x^2+5x-1=0 | | 6+2f=20-3f |

Equations solver categories